Psychological Distress and Dyslipidemia in Chinese Police Officers: A 4-Year Follow-Up Study in Tianjin, China. Issue 4 (April 2015) - Chen, Xi; Leng, Ling; Yu, Hao; Yang, Xi-lin; Dong, Guang-hui; Yue, Song; Chen, Jing-shan; Tang, Nai-jun
Abstract : Objective: This study aimed at investigating whether psychological distress in police officers was associated with dyslipidemia. Methods: A survey was conducted to examine the psychological distress among 5867 police officers in Tianjin, China, from 2007 to 2011. Psychological distress was measured using the Symptom Check List-90-Revised. Cox proportional hazard regression was used to calculate the hazard ratios (HR) of the incidence of dyslipidemia predicted by psychological distress. Results: Among the 3300 participants without dyslipidemia at baseline (2567 with dyslipidemia), 60.5% ( n = 1829) developed incident dyslipidemia 2.61 years (median) later. The adjusted HR was 1.15 (95% confidence interval, 1.05 to 1.26) after the adjustment of police classifications and other variables. The adjusted HR for police officers in charge of traffic control was 1.30 (95% confidence interval, 1.09 to 1.56). Conclusions: Further investigations for associations of psychological factors with dyslipidemia and cardiovascular diseases are needed.